4 months, 3 weeks, and 2 days [videorecording (DVD)] - Mungiu, Cristian, 1968-; Mungiu, Cristian, 1968-; Marinca, Anamaria; Vasiliu, Laura; Ivanov, Vlad (Criterion collection, 2019)
Set during the final days of communism in Romania, two college roommates have twenty-four hours to make the ultimate choice as they finalize arrangements for an illegal abortion.